Penilaian Kinerja Keuangan Perguruan Tinggi Menggunakan Analisis Rasio Keuangan dan Konsep EVA (Economic Value Added) (Studi pada Universitas Nusa Lontar Rote Periode 2019-2021) - Lolu, Margareta; A. Manafe, Henny; Perseveranda, M.E. (Jurnal Ilmu Manajemen Terapan, 2023)
The purpose of this study is to determine the assessment of the company's financial performance using financial ratio analysis and the concept of Economic Value Added (EVA). The research method used is descriptive with a quantitative approach. The object of this research is the University of Nusa Lontar Rote. From all the financial ratio analysis used, it can be concluded that the financial ratios of the University of Nusa Lontar Rote are able to manage assets and capital to increase sales and profits by better financing debt obligations. The financial performance of the University of Nusa Lontar Rote, for the 2019-2021 period, measured from this EVA calculation, has increased every year in the three years of the study period. A high EVA value will attract investors, because the greater the EVA value, the higher the value of the institution, which means the greater the benefits enjoyed. This indicates that the University of Nusa Lontar Rote is able to create added economic value for the institution and is able to meet the expectations of shareholders and investors.